Prevalence of Tinea Capitis among School Children in Obaku, Mbaitoli Local Government Area, Imo State, Nigeria - Udujih, O. G.; Udujih, Helen Ifeoma; Okechukwu , C. C.; KenechukwuDozie , Q. O.; Dozie, U. W. (European Journal of Applied Sciences, 2021)
The prevalence of Tinea capitis among selected primary schools in Ogbaku community, Mbaitoli L.G.A, Imo state was carried out in May, 2017. One hundred and eighty (180) primary school children through random sampling of assenting volunteers attending primary school were recruited into the study. A questionnaire was administered through interview to obtain demograghic information. Physical examinations and laboratory culture of hair stubs/scrapings from scalps was done using standard mycology techniques. The overall prevalence was found to be 30%. The dermatophytes isolated were, Microsporum audonii (66%), Trycophyton mentangrophyte (27%) and Microsporum canis (7%) with M. audonii having the highest prevalence. Females showed a higher prevalence (63%) than males (P<0.05) whereas school children within the age range 11-13 years had the highest prevalence 26(47.27%) followed by those in the age range 8-10 years 42(27.59%) and 5-7 years 12(17.91%). This study has highlighted the need to monitor the practices of barbers and hairstylists and to create awareness among caregivers /school children on hygiene.